Controlled Infection Experiment With Aphanomyces astaci Provides Additional Evidence for Latent Infections and Resistance in Freshwater Crayfish - Francesconi, Caterina; Makkonen, Jenny; Schrimpf, Anne; Jussila, Japo; Kokko, Harri; Theissinger, Kathrin (Frontiers in Ecology and Evolution, 2021)
For 150 years the crayfish plague disease agent Aphanomyces astaci has been the cause of mass mortalities among native European crayfish populations. However, recently several studies have highlighted the great variability of A. astaci virulence and crayfish resistance towards the disease. The main aim of this study was to compare the response of two crayfish species, the European native noble crayfish (Astacus astacus) and the invasive alien marbled crayfish (Procambarus virginalis), to an A. astaci challenge with a highly virulent strain from haplogroup B and a lowly virulent strain from haplogroup A. In a controlled infection experiment we showed a high resistance of marbled crayfish against an A. astaci infection, with zoospores from the highly virulent haplogroup B strain being able to infect the crayfish, but unable to cause signs of disease. Furthermore, we demonstrated a reduced virulence in the A. astaci strain belonging to haplogroup A, as shown by the light symptoms and the lack of mortality in the generally susceptible noble crayfish. Interestingly, in both marbled crayfish and noble crayfish challenged with this strain, we observed a significant decrease of the detected amount of pathogen’s DNA during the experiment, suggesting that this A. astaci haplogroup A strain has a decreased ability of penetrating into the cuticle of the crayfish. Our results provide additional evidence of how drastically strains belonging to A. astaci haplogroup B and haplogroup A differ in their virulence. This study confirmed the adaptation of one specific A. astaci haplogroup A strain to their novel European hosts, supposedly due to reduced virulence. This feature might be the consequence of A. astaci´s reduced ability to penetrate into the crayfish. Finally, we experimentally showed that marbled crayfish are remarkably resistant against the crayfish plague disease and could potentially be latently infected, acting as carriers of highly virulent A. astaci strains.